A Rare Case of a Congenital Nasopharyngeal Ganglioglioma With Dyspnea in a 1-Month-Old Male Infant: A Case Report - Zhao, He; Cao, Zhiwei; Gu, Zhaowei (Frontiers in Pediatrics, 2021)
Background: A ganglioglioma (GG), a tumor with both neuronal and astrocytic components, rarely occurs outside the central nervous system. Case Summary: We present the first reported case of a 1-month-old male with a congenital nasopharyngeal GG, nasal congestion, and dyspnea; we include the operative video. Magnetic resonance imaging was used to explore whether the tumor communicated with the intracranial space. We used an endoscopic plasma technique to ensure complete tumor resection. This afforded a good visual field, endoscopic magnification, and good hemostasis. Conclusions: We report a rare case of a nasopharyngeal GG triggering nasal congestion and dyspnea in a 1-month-old male, and report our experience with the treatment of nasopharyngeal GG and similar diseases.